Association between dietary glycemic index and glycemic load, insulin index and load with incidence of age-related cataract: Results from a case-control study. Issue 3 (May 2020) - Movahedian, Mina; Thomas, Jessica; Rahmani, Jamal; Clark, Cain C.T.; Rashidkhani, Bahram; Ghanavati, Matin
Abstract: Aim: To identify the association between the dietary carbohydrate indexes, such as dietary glycemic index (DGI) and load (DGL), dietary insulin index (DII) and load (DIL), with the possibility of cataract. Method: This case–control study consisted of 101 new cases of cataract and 202 controls. DGI and DGL were computed through DGI values previously published. DII was also calculated based on dietary insulin index data published previously. Results: There was a significant positive association between the highest quartiles of DGI (OR = 6.56; 95% CI = 2.67–16.06; P < 0.001), DGL (OR = 6.17; 95% CI = 1.93–19.37; P = 0.002) and DIL (OR = 4.17; 95% CI = 1.41–12.27; P = 0.004) with risk of cataract, compared to those on the lowest quartile, but not for DII (OR = 0.85; 95% CI = 0.39–1.86; P = 0.82). Furthermore, after stratifying groups by BMI, a significant direct association between highest quartile of DGI (OR = 6.76; 95% CI = 2.49–18.38; P < 0.001) and DGL (OR = 3.45; 95% CI = 0.96–12.37; P = 0.05) with risk of cataract was evident in individuals with elevated BMI (BMI≥25). Conclusion: We found a significant, direct, relationship between DGI, DGL and DIL with risk of cataract. However, the association between DII and the risk of cataract was not significant, even after adjusting for related confounders.